Developing the endurance rower - Clarke , N.; Stellingwerff, T. (2015 World Rowing Coaches Conference, 19-22 Nov 2015, Florida, USA, 2015)
The articles deals with some aspects of developing the endurance rower, for instance performance factors, energy sources, training volume, intensity, polarized training), strength and others.